Two cases of aortic emergency presenting with neurologic manifestations, aided by POCUS - Muhammad Khidir; Nur Hanisah; Farah Alwi; Al-Hilmi Saim (CINQUILL Medical Publishers Inc., 2019)
Acute aortic dissection and aneurysm are lethal vascular emergencies and may present with various clinical presentations including neurological manifestation. Thus, the diagnosis of aortic dissection and aneurysm can be challenging as it may mimic other disorders whereby misdiagnosis can be fatal. In district general hospitals where advanced radiological modalities are not widely available, Point of Care Ultrasound (POCUS) is a tool to diagnose aortic dissection and aneurysm rapidly and accurately. The first case was a 60-year old, Chinese gentleman presented with alternating conscious level. He had a history of syncope that was precipitated by shortness of breath. On examination, his initial GCS was E1,V3, M5 but he regained full consciousness when we laid him supine for intubation. He complained of severe tearing chest pain. He demonstrated radio-radial and radio-femoral delays. Chest X ray showed mediastinal widening, and bedside echocardiography revealed aortic root dilatation with intimal flaps. Patient was sent to a tertiary centre for Computed Tomography of Aorta that confirmed the diagnosis, and vascular repair was planned.The second case was a 70-year old, Malay gentleman presented with recurrent tonic-clonic seizure. On examination, there was a palpable pulsatile mass over epigastric and umbilical region. Bedside ultrasound revealed aortic aneurysm measuring 5.4 x 5.8 cm with peri-aortic haematoma. Despite intense resuscitation, pulseless electrical activity ensued while awaiting for tertiary referral. The presentation of aortic dissection and aneurysm can vary and mimic other deadly diseases in which misdiagnosis can be fatal. Most common neurological manifestations are transient ischaemic attack and ischaemic stroke. POCUS is increasingly used by emergency physician in acute care as it is rapid, non-invasive, widely available and allows accurate measurement of the aorta. Aneurysmal rupture between 4.5 to 5.5 cm is a useful guide for surgical prophylaxis. Intimal flaps visualisation has a sensitivity of 67-80 % and a specificity of 99 -100 %with demonstration of colour flow in both true and false lumens in Doppler, strengthening the diagnosis of aortic dissection. Clinicians should be aware of the unique presentations of aortic dissection and aneurysm, as both can mimic other serious diseases whereby misdiagnosis can be fatal. In district setting where advanced radiological imaging is not readily available, the utility of POCUS in the ED can be crucial to diagnose aortic dissection and aneurysm.